2021
DOI: 10.1007/s10661-021-09013-1
|View full text |Cite
|
Sign up to set email alerts
|

Water balance and influence mechanism analysis: a case study of Hongjiannao Lake, China

Abstract: Hongjiannao groundwater exchange was the largest desert freshwater lake in China (57.25 km 2 in 1986). However, it shrank sharply over the past 34a (1986-2019), with the smallest lake area 31.41 km 2 in 2015. The objective of this study was to use the Landsat images, ASTER GDEM V2 data, and meteorology and statistics data, in combination with the water balance model to calculate the dynamics of water balance elements, quantify and characterize the interannual variations in lakegroundwater exchanges, and analyz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
1
6
1
Order By: Relevance
“…This study provides a valuable supplement to these previous studies and can address the gaps in simulating detailed hydrologic processes related to lakes. In the HJN watershed, previous studies identified precipitation and evaporation (or temperature) as the meteorological driving factors influencing lake variations [68][69][70], and surface runoff and evaporation were identified as the hydrologic driving factors [30]. These results were consistent with the annual mass balance in our study.…”
Section: Comparison With Previous Studiessupporting
confidence: 91%
See 3 more Smart Citations
“…This study provides a valuable supplement to these previous studies and can address the gaps in simulating detailed hydrologic processes related to lakes. In the HJN watershed, previous studies identified precipitation and evaporation (or temperature) as the meteorological driving factors influencing lake variations [68][69][70], and surface runoff and evaporation were identified as the hydrologic driving factors [30]. These results were consistent with the annual mass balance in our study.…”
Section: Comparison With Previous Studiessupporting
confidence: 91%
“…Previous studies have confirmed the effectiveness of utilizing remote-sensed ET data for model evaluation in such areas [42][43][44]. Based on the hydrological characteristics of lakes in semi-arid regions [13,30,58], in addition to the remote-sensed ET data, we also used remotely sensed lake areas and the results from previous studies for model evaluation. The calibration and validation results indicated that the simulated ET was between satisfactory and good in general and underestimation mainly occurred from July to October.…”
Section: Criteria and Results Of Model Evaluationmentioning
confidence: 87%
See 2 more Smart Citations
“…Some evaluation methods are used in developing and utilizing groundwater. These include the water balance method [18,19], numerical simulation method [20,21], isotope tracer method [22], principal component analysis, fuzzy comprehensive analysis, risk matrix method, projection pursuit method [23], and set pair analysis method [24,25]. Among these, set pair analysis can reflect the uncertainty relationship between evaluation indexes and evaluation standards from the three aspects of identity, difference, and opposition.…”
Section: Introductionmentioning
confidence: 99%